Lead-glazed pottery in the lower Moesia and Thrace provinces in the period 1st–5th century AD - Kabakchieva, Gergana (Rei Cretariae Romanae Fautorum Acta, 2022)
The study of lead-glazed pottery from Moesia and Thrace permits to define three groups: The first is from the 1st century AD, the second is the pottery from the 2nd – first half of the 3rd century AD and the third group is from the last quarter of the 3rd – beginning of the 5th century AD. With the beginning of the 2nd century the local, provincial production of the leadglazed pottery in the region started. The variety of the shapes of this pottery is limited as compared to the Red Slip Ware from the same period. During the second half of the 3rd century AD the technology of the lead-glazed pottery changed. The production of the Roman lead-glazed pottery in the eastern part of the Balkan peninsula came to a halt at the end of the 4th and the beginning of the 5th century AD.